The role of isoniazid dosage and NAT2 gene polymorphism in the treatment of tuberculous meningitis - Jian, Yi; Bao, Yuhang; Yang, Fashuang; Zhu, Mei (Frontiers in Immunology, 2025)
BackgroundTuberculous meningitis (TBM) is a non-purulent inflammatory condition affecting the meninges and spinal membranes, caused by Mycobacterium tuberculosis (MTB) infection. This study seeks to explore the impact of varying INH dosages and NAT2 gene polymorphisms on TBM treatment, contributing new insights to improve clinical management and patient prognosis.MethodsPatients with TBM hospitalized between July 2020 and December 2022 were categorized into two groups based on INH dosage: the standard-dose group (300 mg/day) and the high-dose group (600 mg/day). General and baseline data were collected, and NAT2 genotypes were identified using real-time fluorescent PCR with melting curve analysis. The clinical characteristics and outcomes of patients with TBM under varying INH dosages were analyzed.ResultsThis study enrolled 119 patients with TBM, including 32 (26.9%) in the standard-dose group and 87 (73.1%) in the high-dose group. The NAT2 genotypes were distributed as follows: 34 (28.6%) fast acetylators (FA), 73 (61.3%) intermediate acetylators (IA), and 12 (10.1%) slow acetylators (SA). By month 12, 25 patients (21.0%) experienced disability or death, with 22 cases (18.5%) occurring by the end of the 3rd month. Disability and mortality rates differed significantly between the standard-dose and high-dose groups for IA-type TBM patients (P = 0.014). Univariate analysis showed significant differences between groups in baseline focal neurological impairment and disability or mortality by the 3rd and 12th months. Multivariate logistic regression identified INH dosage, cranial nerve palsy, age, and headache as key prognostic factors for TBM.ConclusionHigh-dose INH treatment was associated with a reduced incidence of disability or death compared to the standard-dose regimen, indicating better efficacy and prognosis. In patients with IA-type TBM, the high-dose group showed a significantly lower rate of disability or mortality, suggesting that higher INH dosages may reduce the risk of adverse outcomes.